Race, ethnicity, ancestry, and aspects that impact HLA data and matching for transplant - Madbouly, Abeer; Bolon, Yung-Tsi (Frontiers in Genetics, 2024)
Race, ethnicity, and ancestry are terms that are often misinterpreted and/or used interchangeably. There is lack of consensus in the scientific literature on the definition of these terms and insufficient guidelines on the proper classification, collection, and application of this data in the scientific community. However, defining groups for human populations is crucial for multiple healthcare applications and clinical research. Some examples impacted by population classification include HLA matching for stem-cell or solid organ transplant, identifying disease associations and/or adverse drug reactions, defining social determinants of health, understanding diverse representation in research studies, and identifying potential biases. This article describes aspects of race, ethnicity and ancestry information that impact the stem-cell or solid organ transplantation field with a particular focus on HLA data collected from donors and recipients by donor registries or transplant centers.